2015
DOI: 10.3389/fnmol.2015.00002
|View full text |Cite|
|
Sign up to set email alerts
|

Highly efficient method for gene delivery into mouse dorsal root ganglia neurons

Abstract: The development of gene transfection technologies has greatly advanced our understanding of life sciences. While use of viral vectors has clear efficacy, it requires specific expertise and biological containment conditions. Electroporation has become an effective and commonly used method for introducing DNA into neurons and in intact brain tissue. The present study describes the use of the Neon® electroporation system to transfect genes into dorsal root ganglia neurons isolated from embryonic mouse Day 13.5–16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Pathogen-associated molecular patterns that are associated with pDNA, for example, unmethylated CpG motifs in pDNA, can be recognized by TLR9 and can induce an innate immune response in tissue, which can lead to apoptosis activation [70,71]. pDNA concentrations used in our experiments were higher than concentrations usually used in in vitro experiments, which are most often between 10 and 100 µg/mL [14,[72][73][74][75]. On the other hand, it has been shown that pDNA concentration affects GET efficiency and that, with higher pDNA concentration, efficient GET can also be achieved with shorter pulses [15,16,25,76].…”
Section: Effect Of Pdna Concentration On Overall Gene Electrotransfermentioning
confidence: 81%
“…Pathogen-associated molecular patterns that are associated with pDNA, for example, unmethylated CpG motifs in pDNA, can be recognized by TLR9 and can induce an innate immune response in tissue, which can lead to apoptosis activation [70,71]. pDNA concentrations used in our experiments were higher than concentrations usually used in in vitro experiments, which are most often between 10 and 100 µg/mL [14,[72][73][74][75]. On the other hand, it has been shown that pDNA concentration affects GET efficiency and that, with higher pDNA concentration, efficient GET can also be achieved with shorter pulses [15,16,25,76].…”
Section: Effect Of Pdna Concentration On Overall Gene Electrotransfermentioning
confidence: 81%
“…Primary DRG neurons cannot be effectively transfected using lipofection or electroporation. 41 We employed adenoassociated virus (AAV) vectors as a mode of delivery of opto-iTrkA to DRGs. We constructed AAV PHP.S 42 particles encoding the opto-iTrkA system under the strong, neuronspecific human Synapsin 1 (hSyn) promoter 43 (Figure 1A).…”
Section: ■ Resultsmentioning
confidence: 99%
“…Consistent with previous reports in rat neurons, we found that Cav-1 is expressed by TrkA-positive DRG neurons and is found both in the soma and the neurites [ 16 ] ( Figure 1 A). To get efficient transfection with low amounts of cells, electroporation of DRG neurons was optimized using the Neon ® transfection system [ 37 ]. Using this procedure, we transfected more than 50% of the neurons ( Figure 1 B,C).…”
Section: Resultsmentioning
confidence: 99%
“…All procedures were performed in accordance with French and European legislation on animal experimentation. Primary DRG neurons were prepared from E14.5 mouse embryos and electroporated as previously described [ 37 ] with pEGFP (Clontech, Saint-Germain-en-Laye, France) (0.5 µg) and pCDNA3.1-Cav-1 fused to RFP (gift from Ari Helenius, Addgene Plasmid 14434) [ 38 ] or pCDNA3.1-RFP (1 µg) endotoxin free plasmids (XtraMaxi, Nucleobond, Macherey Nagel, Hoerdt, France). Control RFP was derived from the Cav-1-RFP plasmid.…”
Section: Methodsmentioning
confidence: 99%